2017
DOI: 10.1186/s12909-017-0950-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of International Medical Students In psychosocial medicine

Abstract: BackgroundParticularly at the beginning of their studies, international medical students face a number of language-related, social and intercultural challenges. Thus, they perform poorer than their local counterparts in written and oral examinations as well as in Objective Structured Clinical Examinations (OSCEs) in the fields of internal medicine and surgery. It is still unknown how international students perform in an OSCE in the field of psychosocial medicine compared to their local fellow students.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…In the case of IMS, “financial worries” were among the five most important stressors as the single stressor that was not directly related to the study context, but rather related to the personal or private circumstances of the participants. The issue of financial worries was addressed previously in a study by Huhn et al [ 44 ]. Given the results of this study one can see a difficult financial situation of international students as contributing to a vicious circle, being forced to work to earn money, thus having less time and energy to study or take German language classes, and subsequently eventually scoring even lower in examinations, which, in turn, increases stress rates.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of IMS, “financial worries” were among the five most important stressors as the single stressor that was not directly related to the study context, but rather related to the personal or private circumstances of the participants. The issue of financial worries was addressed previously in a study by Huhn et al [ 44 ]. Given the results of this study one can see a difficult financial situation of international students as contributing to a vicious circle, being forced to work to earn money, thus having less time and energy to study or take German language classes, and subsequently eventually scoring even lower in examinations, which, in turn, increases stress rates.…”
Section: Discussionmentioning
confidence: 99%
“…Acculturation was proposed to influence the communication skills in OSCEs. Huhn et al [15] found that international medical students performed worse especially in the conversational skills stations in the OSCE which was considered as the result of linguistic difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…International medical students worldwide [ 1 ], [ 2 ] as well as in Germany [ 3 ], [ 4 ], [ 5 ] show lower academic performance and a longer duration of study compared to the respective national groups. Medical schools [ 6 ], [ 7 ] and international students themselves [ 8 ] are aware of these academic difficulties as well as of the general problems in coping with the daily life and the integration into the student body.…”
Section: Introductionmentioning
confidence: 99%